In-Plane And Out-Of-Plane Behavior Of Pp-Band Retrofitted Masonry Wallettes - Sathiparan, N.; Mayorca, P.; Nesheli, N.; Guragain, R.; Meguro, K. (New Technologies for Urban Safety of Mega Cities in Asia, 2005)
Unreinforced masonry is one of the most used construction materials in the world. It is also unfortunately, the most vulnerable during earthquakes. This combined with the widespread use of masonry in earthquake prone regions of the world has resulted in a large number of casualties due to the collapse of this type of structures. Several methods have been proposed to improve strength, ductility and energy dissipation capability of masonry structures. However, in developing countries, retrofitting masonry structures should be economic, should be retrofitting material accessible and should be local available workmanship used. Also simple construction procedure is needed. Considering these points, a new retrofitting technique has been proposed based on the use of polypropylene bands (PP-bands), which are commonly utilized for packing. This material is available at a very low price even in remote areas of the world. To evaluate the beneficial effects of the proposed PP-band mesh retrofitting method, diagonal compression tests and out-of-plane tests were carried out on masonry wallettes with and without retrofitting. In diagonal compression tests, the masonry wallettes were retrofitted with meshes whose borders were connected with either epoxy or just by overlapping to evaluate whether the connection type influences the retrofitting performance. From both tests results, which are highlighted in the paper, it could be seen that PP-band retrofitted masonry wallettes had larger residual strength after the first crack in both in-plane and out-of-plane loading. It was clear that PP-band mesh retrofitting improved the overall stability and ductility of the structure.